Effective Treatment of Postherpetic Neuralgia at the First Branch of the Trigeminal Nerve by High-Voltage Pulsed Radiofrequency - Li, Hongxi; Ding, Yuanyuan; Zhu, Yongqiang; Han, Zhenkai; Yao, Peng (Frontiers in Neurology, 2021)
Background: Postherpetic neuralgia (PHN) is one of the most common and serious complications of herpes zoster. PHN of the first branch of the trigeminal nerve is painful and difficult to treat, as no definitive effective treatment is available. The aim of this retrospective study was to observe the efficacy and safety of treatment of PHN of the first branch of the trigeminal nerve with high-voltage pulsed radiofrequency (PRF) of the supraorbital nerve. Methods: Fifty-two patients diagnosed with the PHN of the first branch of the trigeminal nerve at the Department of Pain Management, Shengjing Hospital, China Medical University, between April 2017 and October 2020 were selected. The PRF treatment of the supraorbital nerve was used. The patients were divided into two groups according to the treatment received: group C, conventional PRF group; and group H, high-voltage PRF group. The basic conditions, pain scores, and SF-36 scores of patients before treatment were recorded. Also, intraoperative and postoperative adverse events, visual analog scale (VAS) scores, 36-Item Short Form Health Survey (SF-36) scores at 1 week, 1 month, 3 months, and 6 months of follow-up were recorded. Furthermore, treatment efficiency was followed up at 6 months after treatment. Results: The VAS scores of patients in both groups were significantly lower at all time points after treatment compared with presurgery. VAS scores in group H were lower than those in group C 1, 3, and 6 months after treatment. SF36 scores of patients in group H were better than those in group C 1, 3, and 6 months after treatment. The treatment efficiency at 6 months after treatment was higher in group H than in group C. No serious adverse events occurred in both groups. Conclusion: The efficacy of the high-voltage PRF of the supraorbital nerve in treating the PHN of the first branch of the trigeminal nerve was superior to that of conventional PRF. It was a safe and effective treatment method.